Z dziejów prasy łódzkiej – „Republika” 1923-1925 - Urbaniak, Robert (Acta Universitatis Lodziensis. Folia Historica, 2008)
On the 6th January 1923 the first issue of the “Republika” , the new newspaper, came out. It was founded by Maurycy Ignacy Poznański, Leszek Kirkien, Władysław Polak and Marian Nusbaum-Ołtaszewski - the last one became the editor-in-chief of the newspaper. Since it was published for the rich bourgeoisie, the “Republika”, as the name suggested, was liberal in its character, as well as in the choice of cooperators, and it never got close to any political party. The newspaper dealt with social, literary and trade issues. The head office of the editors was at 49 Piotrkowska Street, whereas the correspondents of the newspaper sent information from many European capitals and Polish cities. The “ Republika” also used information provided by Polish Telegraphic Agency among others. The new publication found readers in Łódź and the region and after its position became well established on the Łódź press market, its daily edition on weekdays was up to 20 thousand copies, and it was the biggest edition among morning newspapers in Łódź in the period described. The “Republika” consisted of thematic sections led by the editiors responsible for them. Due to the connections of the newspaper with Łódź industrial circles, its trade division, “Kurier Handlowy”, whose director was Leszek Kirkien and where Maurycy Ignacy Poznański also published his articles, was well developed and came out regularly. Since the summer of 1925 the publication came into conflict with the authorities, which led to closing down the prosperous newspaper. Its successor the “Ilustrowana Republika” , published since 28th July 1925. It resembled its predecessor with graphic design, layout, themes and choice of editors. The editor-in-chief of the new newspaper became Leszek Kirkien.